Review of distracted driving in young drivers: strategies for management of behavioural patterns. Issue 5 (5th October 2022) - Khan, Abdul Basit; Agrawal, Rajat; Jain, S. S.; Choudhary, Ankit
Abstract: Generally, it is observed, adolescent drivers contribute a major share in motor accident crashes/cases as they are prone to a high level of distraction during driving. Many sundry explanations are monitored behind such cases. An umpteen number of risks which make young drivers more vulnerable to accidents add in high use of electronic appliances, inexperienced drivers, peer involvement during driving and risk-taking tendencies. It can be ameliorated when young drivers are subjected to conditioning at the behavioural level. This review article is an attempt to explore the distraction studies carried out on drivers as well as the behaviour exhibited by them. There is an under-researched area which needs to present programmes related to behavioural changes to target friends, parents and adolescents. This review concludes that a) young drivers under influence of electronic gadgets, peers, music, vehicular adjustments, etc., are more prone to get distracted, b) maximum number of road accidents are due to driver distraction, c) some positive effects have been displayed to curb reckless behaviour at administrative hand by implementing restrictions for drivers and passengers in graduated licensing system. But stricter monitoring is needed d) driving behaviour can be improved by telling the consequences of distracted driving to teenagers as well as their parents through counselling, web-based programs, etc. This review article shows that reproductions of programmes delivered by Web and school-based programs have been assessed with complementary strategies suggested by parents and physicians. These changes are still at an initial stage of progress and eventually will require a controlled application and evaluation studies. Certainly, there is no probable single methodology to avoid the young driver to distraction. But interrelated strategies like accessing usage of other gadgets like cell phones through technological interventions for further development will be helpful.